Factors Influencing Students' Achievements in the Content and Cognitive Domains in TIMSS 4th Grade Science and Mathematics in the United Arab Emirates - Asma Balfaqeeh; Nasser Mansour; Sufian Forawi (MDPI AG, 2022)
Trends in International Mathematics and Science Study (TIMSS) is a comparative international assessment study conducted by the International Association for the Evaluation of Educational Achievement (IEA). TIMSS aims to study how educational opportunities are provided for students and what factors are associated with these opportunities. The purpose of this study was to examine the student factors in the United Arab Emirates that have an association with grade 4 students' TIMSS 2015 results in the content and cognitive domains in the subjects of mathematics and science. The study adopted the quantitative research approach through the data analysis of TIMSS 2015 for grade 4 students in these subjects. The study sample consisted of 21,177 students enrolled in 372 UAE private schools and 186 public schools. The percentage of grade 4 girls who participated in the study was 48%, while the percentage of boys was 52%. A multiple linear regression analysis was conducted to examine the most influential student factors that impact on science and maths achievement. Structural equation modeling (SEM) was implemented to examine the relationships between student factors and the content and cognitive domains of mathematics and science in the TIMSS 2015 results. The findings showed that the student factors with a positive association with student achievement were having breakfast on school days, engaging teaching in mathematics lessons, liking learning science, and confidence in mathematics and science. There was a non-significant correlation between gender and mathematics and science achievement. A surprising finding was that "liking learning mathematics" had a negative association with student performance in that subject. There was a positive association between student engagement and mathematics achievement, while the association between the engagement in science lessons and student performance was found to be insignificant.